Penentuan Prioritas Penerima Dana Bantuan Operasional Pendidikan Lembaga Pendidikan Anak Usia Dini dengan Metode KNN, TOPSIS dan K-Means - Diwahana Mutiara Candrasari; Abdul Syukur; Moch Arief Soeleman (Jurnal Teknologi Informasi - Cyberku (JTIC), 2020)
Education Operational Aid of the Early Childhood Education unit is the financial assistance which is provided to educational institutions, especially for those who engaged in non-formal education, which is used for the process of education in the curriculum of educational institutions in order to give the appropriate and adequate education for students. However, the reality has stated that there is a lot of financial irregularity and inaccuracy of data in the disbursement of the fund of education operational aidat the institute units of Early Childhood Education. On the other hand, there are many complaints that come from the institution itself due to the inaccuracy of data. This research was conducted by applying the KNN, K-Meansalgorithmand TOPSISmethods. The results of the experiment will be tested with two methods that is using cluster distance performance and K-Means cluster count performance. Meanwhile, to measure the level of ranking of TOPSIS method,the experiment will use the percentage calculation method between the experimental data with the implementation of the data to determine the accuracy of TOPSISmethods.